Epidemiology of Penetrating Ocular Trauma - Mumtaz Hussain, Irfan Qayyum Malik, Zeshan Ali, A. Rehman, Muhammad Moin (Pakistan Journal of Ophthalmology, 2018)
Purpose: To study the epidemiology of penetrating ocular trauma at the Institute of Ophthalmology, King Edward Medical University, Mayo Hospital, Lahore Material and Methods: The study was conducted at the Institute of Ophthalmology, Mayo hospital Lahore which included 480 patients. Most of the cases were admitted through emergency. Detailed history was taken with special consideration to the duration of injury and the object causing injury. Visual acuity was recorded using Snellen chart and slit lamp examination included documentation of the size of the tear, its location, involvement of visual axis, iris prolapse, cataract formation, intraocular foreign body (IOFB), and retinal detachment. All cases had pre and post operative B-scan ultrasound. Regular follow up was done and final best corrected visual acuity (BCVA) was recorded. Results: Mean age of patients was 18.24 year with almost 70% ocular trauma occurring in first two decades of life. In first decade male: female ratio was 1.6:1 but it increased to 10:1 after the first decade. Intraocular foreign bodies (IOFB) were found in 15% of cases and iris prolapse in 62.5% cases. Visual axis was involved in 25% of cases.75% of the tears were corneal and 24 % were corneoscleral. Incidence of cataract formation was 61.6%. 35% of trauma was related to sharp objects and 18% to blunt objects. Retinal detachment occurred in 9.81%. Post op Visual acuity was related to the severity of trauma. Conclusion: Prevalence of trauma was much more common in first two decades of life with significantly higher ratio in males than female. Majority of the trauma was caused by sharp objects. Awareness of ocular trauma should